Children's everyday encounters and affective relations with place: experiences of hyperdiversity in Auckland neighbourhoods. (22nd November 2019) - Witten, Karen; Kearns, Robin; Carroll, Penelope; Asiasiga, Lanuola
Abstract: This paper investigates children's experiences of hyperdiversity in public spaces in inner city and suburban neighbourhoods in Auckland, New Zealand. As children walk through, and talk about, their everyday places of play and mobility they sense and reveal material and relational diversity in the places and people they encounter. We examine temporal and affective changes in children's experiences of familiar places when in the presence of strangers – older youth and homeless people. We draw on walking interview and/or focus group data gathered from children aged 9–12 years living in socio economically and ethnically diverse neighbourhoods. Declining rates of physical activity and independent mobility in children and calls for urban spaces that nurture children's agency and wellbeing provide the research context. Ideas of enabling places are adapted to explore the way constructs of otherness, inclusion and difference can be fortified through social and material expressions of hyperdiversity in the urban landscape. We explore the contention that how children and adults behave, identify and feel within particular urban spaces arises from everyday encounters and affective relations with place itself. In so doing, we seek a conceptual broadening of place as an enabler of children's mobility, agency and wellbeing.